Length-based assessment of an exploited coastal pike (Esox lucius) stock (Rügen, southern Baltic Sea) underscores the crucial relevance of growth and natural mortality for assessment outcomes - Colm J. Fitzgerald; Jan S. Droll; Samuel Shephard; Christopher T. Monk; Timo Rittweg; Robert Arlinghaus (Fisheries Research, 2023)

The spawning location of vulnerable ferox trout ( Salmo trutta L. ) in the Lough Corrib and Lough Mask catchments, Western Ireland - Patrick G. Gargan; Finn Økland; Samuel Shephard; Colm Fitzgerald; Martin O'Grady (Journal of Fish Biology, 2021)
Ferox trout are large, long‐lived, piscivorous trout normally found in deep lakes; they are highly prized by trophy anglers. Lough Corrib and Lough Mask, Western Ireland, have recorded the majority of Irish specimen ferox trout since angling records began. Little was known regarding the spawning location of ferox trout relative to sympatric brown trout, and a radio telemetry study was initiated in both catchments in 2005. Over the period 2005–2009, 79 ferox were captured by angling and radio tagged in Lough Corrib, while 55 ferox were tagged in Lough Mask. Manual and helicopter tracking were carried out on all spawning streams entering both lakes over the autumn/winter period to detect tagged fish. Overall, 37 radio‐tagged trout (46.8%) were detected in Lough Corrib streams and 21 tagged trout (38.2%) were recorded from Lough Mask streams. Results from radio tracking indicate that the majority (92%) of ferox trout tagged in Lough Corrib spawned in a single spawning stream, the Cong river, while the majority (76%) of ferox trout tagged in Lough Mask spawned in the Cong canal and Cong river. These results suggest that these streams are most likely the principle spawning locations of ferox trout in both lakes. The occurrence of ferox trout predominantly in single spawning rivers in both catchments highlights the vulnerability of the study ferox populations. As a result of these findings, conservation measures were introduced for ferox trout in both catchments.

Inland fish stock assessment: Applying data‐poor methods from marine systems - Colm J. Fitzgerald; Karen Delanty; Samuel Shephard (Fisheries Management and Ecology, 2018)
Inland fisheries can be diverse, local and highly seasonal. This complexity creates challenges for monitoring, and consequently, many inland fish stocks have few data and cannot be assessed using methods typically applied to industrial marine fisheries. In such situations, there may be a role for methods recently developed for assessment of data‐poor fish stocks. Herein, three established data‐poor assessment tools from marine systems are demonstrated to highlight their value to inland fisheries management. A case study application uses archived length, catch and catch‐per‐unit‐effort data to characterise the ecological status of an important recreational brown trout stock in an Irish lake. This case study is of specific use to management of freshwater sport fisheries, but the broader purpose of the paper was to provide a crossover between marine and inland fisheries science, and to highlight accessible data‐poor assessment approaches that may be applicable in diverse inland systems.